2015
DOI: 10.1093/glycob/cwv039
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of monoclonal antibodies specific for chondroitin sulfate E

Abstract: Chondroitin sulfate E (CSE) is a polysaccharide containing mainly disaccharide units of D-glucuronic acid (GlcA) and 4,6-O-disulfated N-acetyl-D-galactosamine (GalNAc) residues (E-unit) in the amount of ∼ 60%. CSE is involved in many biological and pathological processes. In this study, we established new monoclonal antibodies, termed E-12C and E-18H, by using CSE that contained more than 70% of E-units as an immunogen. These antibodies recognized CSE but not other CSs isomers or dermatan sulfate (DS). We eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…Antibodies against different CS isoforms (CS-A, CS-C, and CS-E) exist but often their specificity toward the individual sulfation patterns is limited, or their epitope is rather small (1-2 disaccharides), leading to antibody crossreactivity with other similar sulfated isoforms (36)(37)(38)(39). The CS-E specific antibody GD3G7 also binds moderately to oversulfated dermatan sulfate (DS) from hagfish (IdoA-GalNac4S6S) and shark skin DS (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibodies against different CS isoforms (CS-A, CS-C, and CS-E) exist but often their specificity toward the individual sulfation patterns is limited, or their epitope is rather small (1-2 disaccharides), leading to antibody crossreactivity with other similar sulfated isoforms (36)(37)(38)(39). The CS-E specific antibody GD3G7 also binds moderately to oversulfated dermatan sulfate (DS) from hagfish (IdoA-GalNac4S6S) and shark skin DS (40).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the antibody also recognizes IdoA, a component of dermatan sulfate and is not exclusively CS specific. A new CS-E specific antibody has recently been reported that can distinguish between iduronic and glucuronic acid and is, similar to D8, specific for CS (and not DS) (39). However, as the GAGs were mostly obtained commercially and purified from natural source, heterogeneity in the CS sulfation patterns is to be expected, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, more focus on targeting the ECM may be an important breakthrough for OC [ 126 ]. Recently, CS-E was established to be overexpressed in OC ECM and made novel molecular target for anti-cancer therapy [ 115 , 129 ].…”
Section: Glycosaminoglycans As a Potential Molecular Target To Stomentioning
confidence: 99%
“…In 2015, Watanabe and co-workers [ 129 ] discovered two novel CS-E specific monoclonal antibodies, E-12C and E-18H. These antibodies were obtained by digesting CS-E fractions rich in the E subunits with hyaluronidase, susceptibly reacting with low sulphation moieties of the CS molecule.…”
Section: Glycosaminoglycans As a Potential Molecular Target To Stomentioning
confidence: 99%
See 1 more Smart Citation